Impact of dynamic pension contribution rates on adequacy of retirement benefits. - Wambugu, Judy Wangari (Strathmore University, 2018)
The retirement income an employee can anticipate is greatly contingent on their salary, contributions, investment strategies and consequently investment returns. Nonetheless, the contributions along with the interest earned are uncertain to be sufficient to cater for the employees' retirement needs. The nature of many pension schemes is to emphasize on the accumulation phase of the contributions with the aim of estimating the retirement benefits, and fail to take into account the forecasting phase of the retirement benefits, by determining the amount of pension a retiree will require in order to cater for their retirement needs. Forecasting retirement needs will ensure pension adequacy by obtaining an adequate target pension income and subsequently an optimum contribution rate that will meet this target pension. This study therefore sought to determine how the contribution rate can be varied, as experience emerges on various parameters including interest earned on contributions and projected retirement salary, with the aim of increasing the likelihood of pension adequacy. However, employers would like stability of their costs, thus they desire to have a fixed contribution rate. It is the member's contribution rate that will be dynamic. Adequacy of the pension income is measured by the degree to which the after-retirement earnings that individuals obtain, can maintain the living standards they had prior to retirement. This measure of adequacy is defined as Income Replacement Ratio(IRR). A stochastic model will be simulated to examine adequacy of retirement benefits and consequently how much the members need to save now in order to achieve that target pension. The study revealed that both the contribution rate and investment strategy adopted in the pension scheme influence the adequacy of retirement benefits. The study recommends that individuals should increase their savings as adequacy of pension income largely depends on how much is being contributed into the pension fund. The pension administrators should also review the investment strategies employed and diversify the investments of the scheme so as to cushion against adverse changes in market conditions.
A Research project submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Science in Actuarial Science at Strathmore University
Keywords: Retirement benefits; Pension; Pension contributions